Validation of Food Compass with a healthy diet, cardiometabolic health, and mortality among U.S. adults, 1999–2018 - O’Hearn, Meghan; Erndt-Marino, Joshua; Gerber, Suzannah; Lauren, Brianna N.; Economos, Christina; Wong, John B.; Blumberg, Jeffrey B.; Mozaffarian, Dariush (Nature communications, 2022)
The Food Compass is a nutrient profiling system (NPS) to characterize the healthfulness of diverse foods, beverages and meals. In a nationally representative cohort of 47,999 U.S. adults, we validated a person’s individual Food Compass Score (i.FCS), ranging from 1 (least healthful) to 100 (most healthful) based on cumulative scores of items consumed, against: (a) the Healthy Eating Index (HEI) 2015; (b) clinical risk factors and health conditions; and (c) all-cause mortality. Nationally, the mean (SD) of i.FCS was 35.5 (10.9). i.FCS correlated highly with HEI-2015 (R = 0.81). After multivariable-adjustment, each one SD (10.9 point) higher i.FCS associated with more favorable BMI (−0.60 kg/m 2 [−0.70,−0.51]), systolic blood pressure (−0.69 mmHg [−0.91,−0.48]), diastolic blood pressure (−0.49 mmHg [−0.66,−0.32]), LDL-C (−2.01 mg/dl [−2.63,−1.40]), HDL-C (1.65 mg/d [1.44,1.85]), HbA1c (−0.02% [−0.03,−0.01]), and fasting plasma glucose (−0.44 mg/dL [−0.74,−0.15]) ; lower prevalence of metabolic syndrome (OR = 0.85 [0.82,0.88]), CVD (0.92 [0.88,0.96]), cancer (0.95 [0.91,0.99]), and lung disease (0.92 [0.88,0.96]); and higher prevalence of optimal cardiometabolic health (1.24 [1.16,1.32]). i.FCS also associated with lower all-cause mortality (HR = 0.93 [0.89,0.96]). Findings were similar by age, sex, race/ethnicity, education, income, and BMI. These findings support validity of Food Compass as a tool to guide public health and private sector strategies to identify and encourage healthier eating. The Food Compass is a nutrient profiling system to characterize the healthfulness of diverse foods, beverages and meals. In a nationally representative cohort of 47,999 U.S. adults, the authors validate a person’s individual Food Compass Score against health outcomes.